Acid-Base Disorders: Interpretation of the Stewart Approach - Stanie, Shianita; Juni Kurniawaty; Sudadi (Jurnal Komplikasi Anestesi, 2026)
Comprehension of physiological consequences arising from acid-base disturbances, together with manageable factors such as ventilation and perfusion that rapidly affect acid-base balance, is essential for anesthesiologists. The application of the Stewart acid-base model has advanced the mechanistic understanding of acid-base physiology. This model incorporates shifts in ions, including Cl-, K+, Na+, and PO43-, as well as the buffering capacity of albumin, to detect acid-base disorders. The Stewart approach is superior for identifying subtle and otherwise undetectable metabolic changes. It is founded on three core principles: electroneutrality, dissociation equilibria of incompletely dissociated substances, and mass conservation. In the Stewart method, [HCO3-] and pH in body fluids represent dependent variables determined by three independent variables: total CO2, strong ion difference (SID), and total weak non-volatile acid concentration (ATOT), which is primarily governed by albumin and phosphate levels.